2008
DOI: 10.1186/bcr1996
|View full text |Cite
|
Sign up to set email alerts
|

NVP-AUY922: a small molecule HSP90 inhibitor with potent antitumor activity in preclinical breast cancer models

Abstract: Introduction Heat shock protein 90 (HSP90) is a key component of a multichaperone complex involved in the posttranslational folding of a large number of client proteins, many of which play essential roles in tumorigenesis. HSP90 has emerged in recent years as a promising new target for anticancer therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
162
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(169 citation statements)
references
References 31 publications
7
162
0
Order By: Relevance
“…VER-155008 binds in the ATPase site of Hsc70/Bag-1 and the adenosine portion of VER-155008 adopts corresponding protein interactions as the adenosine portion of ATP. The additional potency of VER-155008 is likely through the displacement of a water group and the We have previously shown that following Hsp90 inhibition with NVP-AUY922 or 17-AAG, deferential caspase dependent apoptotic responses are observed [26,27]. For example, the Her2 positive breast carcinoma BT474 undergoes massive caspase dependent apoptosis while the colon carcinoma cell line HCT116 does not.…”
Section: Ver-155008 Is a Potent Inhibitor Of The Hsp70 Family Of Chapmentioning
confidence: 99%
“…VER-155008 binds in the ATPase site of Hsc70/Bag-1 and the adenosine portion of VER-155008 adopts corresponding protein interactions as the adenosine portion of ATP. The additional potency of VER-155008 is likely through the displacement of a water group and the We have previously shown that following Hsp90 inhibition with NVP-AUY922 or 17-AAG, deferential caspase dependent apoptotic responses are observed [26,27]. For example, the Her2 positive breast carcinoma BT474 undergoes massive caspase dependent apoptosis while the colon carcinoma cell line HCT116 does not.…”
Section: Ver-155008 Is a Potent Inhibitor Of The Hsp70 Family Of Chapmentioning
confidence: 99%
“…Significant antitumor activity was also observed when the compound was administered on a weekly i.v. schedule (Jensen et al, 2008). NVP-AUY922 has entered phase I clinical trials.…”
Section: Phospholipids-antagonists Of Ph Domainsmentioning
confidence: 99%
“…Antitumor efficacy ranges from minimal effects to tumor growth stasis but rarely tumor regression (9,14,15,(18)(19)(20). The variance in response between xenograft models may be attributable to differences in client protein dependence on Hsp90, tumor dependence on the client protein, kinetics of client protein degradation, and resynthesis, as well as, drug pharmacokinetic and pharmacologic properties.…”
Section: Introductionmentioning
confidence: 99%
“…All other Hsp90 inhibitors are fully synthetic small molecules that fall into distinct structural classes including: (i) resorcinol-containing molecules (NVP-AUY922, KW-2478, STA-9090, and AT13387), (ii) purine scaffold (BIIB021, PU-H71, and MPC-3100), (iii) imidazopyridine (Debio 0932), (iv) 2-aminoterephthalamide (XL888), and (v) aminopyrimidine (NVP-HSP990). The chemical structures of BIIB028 and DS- 2248 have not yet been disclosed (5)(6)(7)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation